POSSIBILITY OF PREPARATION OF THE STUDENTS OF TEACHING PROFESSION FOR THE 1ST LEVEL OF PRIMARY SCHOOL IN THE AREA OF ICT - MANĚNOVÁ, Martina (Trends in education, 2009)
The Frame Educational Programme determines for the 1st level of primary school a new obligatory educational area: Informative and commutative technology. Even the Pedagogical Faculties, which prepare the students for teaching profession for the 1st level of primary school, should react to this reality. The study informs about the conception of students preparation of the above mentioned branch at the Pedagogical Faculty of University, Hradec Králové.
Keywords: information and communitation technology; The Frame Educational Programme; primary school.